Fate of zinc and silver engineered nanoparticles in sewerage networks. (15th June 2015) - Brunetti, Gianluca; Donner, Erica; Laera, Giuseppe; Sekine, Ryo; Scheckel, Kirk G.; Khaksar, Maryam; Vasilev, Krasimir; De Mastro, Giuseppe; Lombi, Enzo
Abstract: Engineered zinc oxide (ZnO) and silver (Ag) nanoparticles (NPs) used in consumer products are largely released into the environment through the wastewater stream. Limited information is available regarding the transformations they undergo during their transit through sewerage systems before reaching wastewater treatment plants. To address this knowledge gap, laboratory-scale systems fed with raw wastewater were used to evaluate the transformation of ZnO- and Ag-NPs within sewerage transfer networks. Two experimental systems were established and spiked with either Ag- and ZnO-NPs or with their dissolved salts, and the wastewater influent and effluent samples from both systems were thoroughly characterised. X-ray absorption spectroscopy (XAS) was used to assess the extent of the chemical transformation of both forms of Zn and Ag during transport through the model systems. The results indicated that both ZnO- and Ag-NPs underwent significant transformation during their transport through the sewerage network. Reduced sulphur species represented the most important endpoint for these NPs in the sewer with slight differences in terms of speciation; ZnO converted largely to Zn sulfide, while Ag was also sorbed to cysteine and histidine. Importantly, both ionic Ag and Ag-NPs formed secondary Ag sulfide nanoparticles in the sewerage network as revealed by TEM analysis. Ag-cysteine was also shown to be a major species in biofilms. These results were verified in the field using recently developed nanoparticle in situ deployment devices (nIDDs) which were exposed directly to sewerage network conditions by immersing them into a municipal wastewater network trunk sewer and then retrieving them for XAS analysis. Graphical abstract: Highlights: Transformation of zinc oxide and silver nanoparticles were simulated in a lab-scale sewerage network. Similarly to ionic Zn, ZnO-NPs were transformed to zinc sulfide. Ionic Ag and Ag-NPs were converted largely to silver sulfide or bound to amino acids.